A. Conan Doyle "The War In Bahemia" Anthroponyms In Artistic Works From The English Language Analysis Of The Translation Into Uzbek - Iroda Jurayeva Ahmedovna (Open Academia, 2024)
This article is from a series of novels written by A. Conan Doyle translation of anthroponyms from English to Uzbek and their analyzed taking into account the factors affecting the reader's understanding of the text from a linguistic point of view. Since the names chosen as objects are textures, before the names of the characters, their function and character in the work was invented, and then it was put into linguistic patterns. Because of this, the article offers templates for etymological, lexicological, semantic and phonetic analysis before translating them into Uzbek
Keywords: lexicology; anthroponyms; transliteration